Rehabilitation of the Doce River Basin after the Fundão dam collapse: What has been done, what can be done and what should be done? - Cordeiro, Juni; Gomes, Alessandra R.; Santos, Carlos Henrique B. [UNESP]; Rigobelo, Everlon Cid [UNESP]; Baptista, Marcio B.; Moura, Priscilla Macedo; Scotti, Maria Rita (Wiley, 2022)
Five years after the failure of the Fundão Dam in Brazil, no scientific report has been published regarding the rehabilitation interventions performed by the Renova Foundation, which is solely responsible for the rehabilitation of the Doce River Basin. This study aimed to assess the fluvial and riparian rehabilitation efforts performed by Renova, as well as to test and propose alternatives, when appropriate. Before the dam rupture, the fluvial system showed a single-thread morphology that was sinuous and meandering. After the rupture, changes occurred in the river dynamics with strong sediment deposition in riparian areas, resulting in the loss of several meandering streams, oxbow-lakes, lagoons, and fluvial islands. There was also a loss of the riparian vegetation, from 61% to 6%, as estimated by the Normalized Difference Vegetation Index (NDVI). Renova subjected nearly 61% of the study area to fluvial rehabilitation techniques, particularly using rip-rap or larssen sheet piling (37%) and erosion control fibre blankets (17%). However, 50% of these interventions have been unsuccessful because the rip-rap was poorly positioned and the biodegradable fibre blankets decomposed rapidly. We recommend changing the position of the rip-rap from convex to concave banks and to avoid using biodegradable fibre blankets. Instead, we encourage the planting of riparian forests with native species to form buffer zone systems. Renova' riparian rehabilitation attempts were found to have low success rates, which was attributed to the unaddressed presence of toxic compounds, such as sodium and ether amine. However, our results proved that riparian rehabilitation using native species is feasible, if physical, chemical, biological, and phyto-remediation strategies are adopted, to alleviate the ether amine and sodium toxicity.